2018
DOI: 10.1111/anu.12874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary zinc oxide and selenium nanoparticles on growth performance, immune responses and enzyme activity in rohu,Labeo rohita(Hamilton)

Abstract: Zinc is the second most abundant trace element in the animal body.It cannot be stored in the body (Zalewski et al., 2005) and can be consumed as regular dietary intake to meet the physiological need of the body. As a component of numerous enzymes and hormones, it is necessary for the proper physiological functioning (Prasad, 1991).Several important enzymatic activities like alcohol dehydrogenase, alkaline phosphatase (ALP), aldolase, lactate dehydrogenase (LDH), RNA and DNA polymerases, reverse transcriptase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…This suggests that the neutrophils were stimulated to release lysozyme in the presence of nanoparticles. Similarly, dietary zinc oxide and selenium nanoparticle feed were revealed to enhance the lysozyme activity in Labeo rohita (Swain et al 2018), β-1,3 glucan binding protein-based zinc oxide nanoparticle elevated lysozyme activity (Anjugam et al 2018) which are in line with the present investigation. Only a few studies have been reported so far that determined the lysozyme activity in fish after treating it with nanoparticles.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that the neutrophils were stimulated to release lysozyme in the presence of nanoparticles. Similarly, dietary zinc oxide and selenium nanoparticle feed were revealed to enhance the lysozyme activity in Labeo rohita (Swain et al 2018), β-1,3 glucan binding protein-based zinc oxide nanoparticle elevated lysozyme activity (Anjugam et al 2018) which are in line with the present investigation. Only a few studies have been reported so far that determined the lysozyme activity in fish after treating it with nanoparticles.…”
Section: Discussionsupporting
confidence: 90%
“…Serum was separated from the blood (without EDTA) by centrifuging at 2000 g for 15 min at 4°C' (Swain et al, 2019).…”
Section: Sampling Of Fishmentioning
confidence: 99%
“…The total fish biomass per pond was measured at the beginning of the feeding trial and subsequently at the end of the trial Blood collection was done at the end of the experimental trial by randomly selecting 10 fishes from each pond. Blood and serum samples of fish were used for laboratory analyses (Swain et al, 2018).…”
Section: Pond Preparationmentioning
confidence: 99%
“…Bacterial agglutination test was carried out in "U" shaped microtitre plates as the method described by Swain et al (2018). A 25 μl of fish serum sample was two fold serially diluted and added in each well with an equal volume of normal saline solution (NSS).…”
Section: Bacterial Agglutination Activitymentioning
confidence: 99%